Assessment of progesterone levels on the day of pregnancy test determination: A novel concept toward individualized luteal phase support - Racca, A.; Alvarez, M.; Garcia Martinez, S.; Rodriguez, I.; Gonzalez-Foruria, I.; Polyzos, NP.; Coroleu, B. (Frontiers in Endocrinology, 2023)
Research question The main objective of the study is to define the optimal trade-off progesterone (P4) values on the day of embryo transfer (ET), to identify low P4-human chorionic gonadotropin (hCG), and to establish whether P4 supplementation started on the hCG day can increase the success rate of the frozen embryo transfer (FET) cycle. Design A single-center, cohort, retrospective study with 664 hormone replacement therapy (HRT)-FET cycles analyzed female patients who received vaginal 600 mg/day of P4 starting from 6 days before the FET, had normal P4 values on the day before ET, and whose P4 on the day of the pregnancy test was assessed. Results Of the 664 cycles, 69.6% of cycles showed P4 ≥ 10.6 ng/ml, while 30.4% showed P4 < 10.6 ng/ml on the day of the hCG. Of the 411 chemical pregnancies detected, 71.8% had P4-hCG ≥ 10.6 ng/ml (group A), while 28.2% had P4-hCG < 10.6 ng/ml. Of the cycles with P4-hCG < 10.6 ng/ml, 64.7% (group B) were supplemented with a higher dose of vaginal P4 (1,000 mg/day), while 35.3% (group C) were maintained on the same dose of vaginal micronized P4. The live birth rate was 71.9%, 96%, and 7.3% for groups A, B, and C, respectively. Conclusion The likelihood to detect P4-hCG < 10.6 ng/ml decreased as the level of serum P4 the day before ET increased. The live birth rate (LBR) was shown to be significantly lower when P4 was low and not supplemented.